The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.heliyon.2020.e04597
|View full text |Cite
|
Sign up to set email alerts
|

A modelling study to evaluate the effect of impure CO2 on reservoir performance in a sandstone saline aquifer

Abstract: Carbon capture and storage (CCS) is expected to play a key role in meeting greenhouse gas emissions reduction targets. In the UK Southern North Sea, the Bunter Sandstone formation (BSF) has been identified as a potential reservoir which can store very large amounts of CO 2 . The formation has fairly good porosity and permeability and is sealed with both effective caprock and base rock, making CO 2 storage feasible at industrial scale. However, when CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The experiment of Zhao et al showed that pore structures were affected during CO 2 injection, in which the precipitation of secondary minerals changed the sorting behavior of the rock formation, especially the pore throats, causing the permeability to decline . The change in pore throats is because of the strong precipitation of carbonate minerals, feldspar and quartz. ,,, The results of the experiment of Zhao et al. are presented in Figure .…”
Section: Concept Of Formation Damage During Co2 Sequestrationmentioning
confidence: 99%
“…The experiment of Zhao et al showed that pore structures were affected during CO 2 injection, in which the precipitation of secondary minerals changed the sorting behavior of the rock formation, especially the pore throats, causing the permeability to decline . The change in pore throats is because of the strong precipitation of carbonate minerals, feldspar and quartz. ,,, The results of the experiment of Zhao et al. are presented in Figure .…”
Section: Concept Of Formation Damage During Co2 Sequestrationmentioning
confidence: 99%
“…CO 2 storage in geological formations is considered to be an effective option to store it permanently and safely . The geological formation used includes deep saline aquifers, depleted oil and gas fields, storage in basalts, storage in coal, deep ocean, and hydrate formation . However, the main driving factor used to assess the storage requirements for the location include depth of the formation (more than 800 m), storage capacity, permeability and porosity, physical leakage, hydrogeology conditions, and seismicity activities …”
Section: Introductionmentioning
confidence: 99%